2021
DOI: 10.1088/1748-9326/abd430
|View full text |Cite
|
Sign up to set email alerts
|

SolarEV City concept: building the next urban power and mobility systems

Abstract: Cities have become the focus of global climate mitigation efforts because as they are responsible for 60%–70% of energy-related CO2 emissions. As the world is increasingly urbanized, it is crucial to identify cost-effective pathways to decarbonize and enhance the resilience of cities, which ensure the well-being of their dwellers. Here, we propose a ‘SolarEV City’ concept, in which integrated systems of cities’ roof-top photovoltaics and electric vehicles (EVs) supply affordable and dispatchable CO2-free elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 60 publications
2
29
0
Order By: Relevance
“…In a city scale, rooftop PVs coupled with electric vehicles (EV) are possibly highly effective tools to decarbonize urban energy systems [5,6]. EVs are important means to decarbonize transport sector by replacing internal combustion of fossil fuels with electricity, but also play roles as energy storage for VRE such as rooftop PVs [25] or wind power [51].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a city scale, rooftop PVs coupled with electric vehicles (EV) are possibly highly effective tools to decarbonize urban energy systems [5,6]. EVs are important means to decarbonize transport sector by replacing internal combustion of fossil fuels with electricity, but also play roles as energy storage for VRE such as rooftop PVs [25] or wind power [51].…”
Section: Discussionmentioning
confidence: 99%
“…EVs are important means to decarbonize transport sector by replacing internal combustion of fossil fuels with electricity, but also play roles as energy storage for VRE such as rooftop PVs [25] or wind power [51]. It has been shown that rooftop PVs combined with EVs in a city scale can supply up to 95% of electricity to cities in Japan [6]. In the case of the special districts of Tokyo including Shinagawa, the PV plus EV systems can supply 53% of the annual demands.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations